A new species of Geophagus (Teleostei: Cichlidae): Naming a cichlid species widely known in the aquarium hobby as 'Geophagus sp. Tapajos red head'. Issue 6 (9th October 2022) - Chuctaya, Junior; Nitschke, Pedro; Andrade, Marcelo C.; Wingert, Juliana; Malabarba, Luiz R.
Abstract: A new species of Geophagus sensu stricto is described from the Tapajos River basin, Brazil, elevating the number of species of the genus to 21. The new species is of commercial importance and is known in the aquarist trade as Geophagus 'red head'. The new species is diagnosed using an integrative approach, based on mitochondrial DNA analysis along with morphological evidence. The new species is distinguished from all congeners by the absence of markings on the head, the bar pattern composed by nine vertical bars on the flanks and the presence of distinct longitudinal bands in the caudal fin. Additionally, it shows a genetic distance of at least 2.0% in cytochrome b gene sequences from its closest congeners. Molecular analysis including most genera of Cichlidae from South America corroborates that the new species belongs to the group of Geophagus sensu stricto .